2014
DOI: 10.4490/algae.2014.29.1.027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of solar UV radiation on photosynthetic performance of the diatom Skeletonema costatum grown under nitrate limited condition

Abstract: Availability of nutrients is known to influence marine primary production; and it is of general interest to see how nutrient limitation mediates phytoplankton responses to solar ultraviolet radiation (UVR, 280-400 nm). The red tide diatom Skeletonema costatum was cultured under nitrate (N)-limited and N-replete conditions and exposed to different solar irradiation treatments with or without UV-A (315-400 nm) and UV-B (280-315 nm) radiation. Its photochemical quantum yield decreased by 13.6% in N-limited cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
(50 reference statements)
1
0
0
Order By: Relevance
“…Low N often limits phytoplankton growth (Mei et al 2011; Moore et al 2013; Li and Gao 2014) as indeed found here for T. pseudonana (Fig. 1a).…”
Section: Discussionsupporting
confidence: 83%
“…Low N often limits phytoplankton growth (Mei et al 2011; Moore et al 2013; Li and Gao 2014) as indeed found here for T. pseudonana (Fig. 1a).…”
Section: Discussionsupporting
confidence: 83%
“…Nitrogen is a major material to build up cells; therefore, a low media N level is usually believed to limit phytoplankton growth (Li and Gao, 2014;Mei et al, 2011;Moore et al, 2013) as found here for T. pseudonana (Fig. 1a).…”
Section: Discussionmentioning
confidence: 53%